ATSAR ISTIKHDAM AL-SHUWAR AL-WARIDAH FIZ AL-NUSHISH AL-'ARABIYAH FIZ MUYIL TALAMIDZ ILA MAHARAH AL-QIRAAH - Fahmi, Chairul (Arabi : Journal of Arabic Studies, 2018)
This study aimed to find out the weakness of the students of Islamic Junior High School Darul Ma'arif Jakarta in learning qira>'ah, the lack of students who like qira>'ah lessons, and the weak ability of the students to understand Arabic language. This research also tried to know how to use text in Arabic in learning qira>'ah. This research was a quantitative research using the method of measurement between variables, namely the use of illustrations and interest in learning by using purposive sampling. Various research data were collected through interviews, direct observation, questionnaire division, and test implementation. This study showed that there was no influence of the use of illustration in Arabic text toward the students' interest in learning qira>'ah.